Panitumumab in combination with infusional oxaliplatin and oral capecitabine for conversion therapy in patients with colon cancer and advanced liver metastases. Issue 19 (18th July 2013) - Leone, Francesco; Artale, Salvatore; Marino, Donatella; Cagnazzo, Celeste; Cascinu, Stefano; Pinto, Carmine; Fornarini, Giuseppe; Tampellini, Marco; Di Fabio, Francesca; Sartore‐Bianchi, Andrea; De Carlis, Luciano; Pugliese, Raffaele; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Preoperative chemotherapy improves the outcome in patients with colorectal cancer with liver metastases. In the current study, the authors evaluated the activity of a conversion treatment with the combination of capecitabine plus oxaliplatin (XELOX) used in association with panitumumab in patients with unresectable, liver‐only, metastatic colon cancer. METHODS Chemotherapy‐naive patients with unresectable liver metastases from colon cancer with no other metastatic disease sites were enrolled. All patients received upfront therapy with XELOX plus panitumumab (P‐XELOX) and were reevaluated for resectability every 4 cycles. The primary endpoint was the objective response rate (ORR). Secondary endpoints were overall survival (OS), progression‐free survival, the percentage of patients whose disease became radically resectable, and the safety of the P‐XELOX combination. RESULTS A total of 49 patients were recruited, 35 of whom had wild‐type KRAS (wtKRAS) and 14 of whom (who were enrolled before study amendment) had unknown (9 patients) or mutated (5 patients) KRAS mutational status. Forty‐six patients were evaluable for response. After conversion P‐XELOX therapy, the ORR in the general population was 54%, with 2 complete responses, 23 partial responses, and 14 cases of stable disease. In patients with wtKRAS, the ORR of the patients reached 65% (2 CRs and 19 PRs), which allowed 15 patients with initial unresectable liver metastasis to be reclassified as having resectable disease. Survival analysis demonstrated a median progression‐free survival of 8.5 months and a median OS of 21.9 months. Patients who underwent surgery were found to have a significantly better OS when compared with those who did not undergo surgery (P < .001). Overall, toxicities were found to be predictable and manageable, with the most common being cutaneous, gastrointestinal, and neurologic toxicities. CONCLUSIONS Conversion P‐XELOX therapy yields high response and resectability rates for patients with metastatic colon cancer with extensive liver involvement. Cancer 2013;119:3429–3435.. © 2013 American Cancer Society.